2015
DOI: 10.1063/1.4937626
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of surface charge accumulation on Al2O3-filled epoxy resin insulator under dc voltage by direct fluorination

Abstract: Surface charge accumulation on insulators under high dc voltage is a major factor that may lead to the reduction of insulation levels in gas insulated devices. In this paper, disc insulators made of Al2O3-filled epoxy resin were surface fluorinated using a F2/N2 mixture (12.5% F2) at 50 °C and 0.1 MPa for different durations of 15 min, 30 min and 60 min. A dc voltage was applied to the insulator for 30 min and the charge density on its surface was measured by an electrostatic probe. The results revealed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Moreover, it seems that gas-phase fluorination exerted a more significant influence on the electron trap than the hole trap, which may be attributed to the different main conduction approach of hole and electron. The hole valence band states have an intra-chain character as opposed to inter-chain for electron conduction [24], so the injected hole will be deeply trapped in the intra-chain defects along the chain backbone while the electron would be captured by the trap in the amorphous regions. Therefore, as the amorphous space expands, the effect of gas-phase fluorination on electron trap would become more pronounced.…”
Section: Surface Charge Accumulation and Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it seems that gas-phase fluorination exerted a more significant influence on the electron trap than the hole trap, which may be attributed to the different main conduction approach of hole and electron. The hole valence band states have an intra-chain character as opposed to inter-chain for electron conduction [24], so the injected hole will be deeply trapped in the intra-chain defects along the chain backbone while the electron would be captured by the trap in the amorphous regions. Therefore, as the amorphous space expands, the effect of gas-phase fluorination on electron trap would become more pronounced.…”
Section: Surface Charge Accumulation and Dissipationmentioning
confidence: 99%
“…For example, various kind of plasma treatments of cellulose paper have been utilized to enhance their hydrophobicity [18][19][20]. As one of the most commonly used surface modification method, gas-phase fluorination has already been used to modify the surface charge and space charge dynamics of polymer such as polyethylene, polypropylene, polyimide and epoxy resin [21][22][23][24]. Previous studies also show that the surface charge dissipation of oil-impregnated cellulose insulation paper under DC and pulse voltage could be accelerated by gas-phase fluorination [25].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the direct fluorination has shown preferable results in a wide range of industry application because it can tailor the surface property of dielectric materials without compromising the bulk performance. [11][12][13] By controlling treatment factors during the direct fluorination process, a surface layer containing C-F bonds with preferable surface properties can be obtained. 14,15 In An's research, by controlling direct fluorination time and temperature, different surface conductivities are obtained in epoxy resins.…”
Section: -2mentioning
confidence: 99%
“…For example, Zhang et al used a direct fluorination method to gradientize the insulator filled with Al 2 O 3 ,and it was found that the introduction of fluorine ions not only changed the physical and chemical properties of the insulator surface, but also effectively inhibiting the accumulation of surface charges and reducing the surface trap depth. [15] The method of material coated with inorganic film usually refer to deposit an oxide film on the surface of the material. He et al used a magnetron sputtering method to form a Cr 2 O 3 film on the surface of epoxy resin, and this film restrict charges injected into the surface of the epoxy resin under high voltage.…”
Section: Introductionmentioning
confidence: 99%